The choice of apportionment factors under formula apportionment - Marco Runkel; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper investigates the choice of apportionment factors under a corporate tax system of Formula Apportionment. In contrast to perceived wisdom, we show that the apportionment formula contains both mobile (capital) and immobile (labor) factors if jurisdictions are granted full fiscal autonomy with respect to tax rates and the formula design. A welfare gain can be realized by delegating the decision over apportionment factors to a central planner (centralization), while at the same time allowing jurisdictions fiscal autonomy in setting tax rates. However, the central planner uses the formula as a corrective instrument to internalize fiscal externalities and, therefore, uses mobile apportionment factors as well.
Keywords: H25; H71; H87; 330; Formula Apportionment; Körperschaftsteuer; Steuerbemessung; Multinationales Unternehmen; Wohlfahrtseffekt; Theorie